2015
DOI: 10.1016/j.biopsycho.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Tonic and phasic co-variation of peripheral arousal indices in infants

Abstract: HighlightsPrevious ANS research is largely based on individual peripheral measures.We recorded HR, EDA, pupil size and head and peripheral accelerometry.We found high covariation between ANS indices in infants.Pupil size and EDA showed more complicated patterns.Different patterns were seen between tonic and phasic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 80 publications
(97 reference statements)
6
55
0
Order By: Relevance
“…They were recorded by a Tobii TX300 eyetracker. The process used to extract this data is described in (Wass et al, 2015).…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…They were recorded by a Tobii TX300 eyetracker. The process used to extract this data is described in (Wass et al, 2015).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Although detailed socio-economic or ethnic data were not collected as part of this study, it should be noted that the recruitment area is a relatively wealthy, university town. Autonomic data collected from a subset of these infants (37) forms the basis for a previous paper looking at patterns of covariation between different autonomic measures (Wass et al, 2015). However, the present paper contains completely new analyses, addressing overlapping research questions, as described in detail in the Introduction.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same session, we also measured infants' physiological reactivity, indexed as heart rate acceleration while infants watched a video of another infant crying. In previous research we have shown that heart rate shows strong patterns of phasic covariation with other widely used measures of arousal such as electrodermal activity and movement patterns (Wass, Clackson & de Barbaro, 2015), validating its use as a single measure to index arousal.…”
Section: Running Head: Stress Reactivity and Attention In Infantsmentioning
confidence: 99%